Limnologia e sensoriamento remoto: qualidade da água do Rio Miriti (Manacapuru/AM) e contribuição para a gestão dos recursos hídricos - Ferreira Júnior, João Carlos (2019)
The use of geotechnical tools is not recent in aquatic studies, and it is becoming increasingly frequent and necessary for water resources management. This study aimed to evaluate the potential use of geoprocessing and remote sensing techniques applied to water resources to identify aquatic compartments and to monitor water quality in the lower Miriti river, as a contribution to implementation of water resources management instruments. The methodological procedures were based on the construction of a geographic database: 1) the use of DEM for delimiting the hydrographic basin and acquisitioning geomorphometric data; 2) remote sensing image processing, applying slicing and transformation of spectral bands; 3) mapping land use and vegetation cover, besides the measurement and spatialization of limnological data (temperature, turbidity, transparency, pH, dissolved oxygen, total dissolved solids and electrical conductivity); 4) discussion about the use of geotechnical tools applied to water resources management instruments. The use of geoprocessing and remote sensing techniques applied to water resources are important tools for water management. The use of altimetric data was important to understand the hydrological functioning of the basin, besides contributing to understand the planning of the territorial organization. Six prevailing uses of water in the lower Miriti river were also identified, with two consumptive uses (urban/rural human consumption and animal consumption) and four non-consumptive uses (effluent, tourism/leisure, fishing/aquaculture and navigation). The spatialization of the limnological data allowed direct correlations with land uses, with associations to input materials of natural and/or anthropic origin. Finally, the remote sensing data contributed as complementary data in the analysis of water quality, by the historical data, as well as the monitoring of the optically active constituents, evidencing a spatiotemporal increase of the water reflectance in the three bands of the visible band (RGB), associated with urban and agricultural expansion. In summary, the realization of this work denotes the relevance of the basin in both municipal and regional context, evidencing the necessity of a greater action by the public power and other involved actors regarding water resources conservation and other wealths of the basin. Finally creating a management institution concerned directly and exclusively with the water issue can be a feasible alternative for managing this area.